What works in activation policies for young unemployed with problems besides unemployment? - Bredgaard, Thomas; Hansen, Charlotte (Tidsskrift for Arbejdsliv, 2012)
Denmark has been one of the pioneers in active labour market policies and has inspired the development of the European Employment Strategy. In the Danish media, however, activation policies for the unemployed are often criticized for being meaningless, abusive and wasteful of public resources. This is especially the case for the long-term unemployed on social assistance, who have a number of social, psychological and physical problems beyond unemployment. In this article we apply an evaluation method – realistic evaluation – which has not previously been applied systematically in the evaluation of the outcomes of Danish active labour market policies. The method seeks to specify the mechanisms and contexts that create specific outcomes. It is a middle ground and supplement to the more traditional controlled experiments and effect evaluations on the one hand, and case studies and process evaluations on the other hand. Realistic evaluation seeks to build contextualized but generalized knowledge about what works, how it works for whom and under which conditions. We study three cases of activation projects for young unemployed with problems besides unemployment. We construct and validate program theories for the projects. The program theories consist of mechanisms, moderators and intermediate objectives that need to be present in order to retain the target group in a realistic choice of ordinary employment or education.